The potential use of brewers' spent grain-based substrates as horticultural bio-fertilizers - Bianco, Angela; Melito, Sara; Garau, Matteo; Giannini, Vittoria; Zara, Giacomo; Assandri, Davide; Oufensou, Safa; Coronas, Roberta; Pampuro, Niccolò; Budroni, Marilena (Frontiers in Sustainable Food Systems, 2024)
Introduction: Brewers’ Spent Grain (BSG) is the most important by–product of breweries. Nowadays the main way of recycling BSG is represented by livestock feed production, due to its high content in fiber, non–degradable protein, and water–soluble vitamins. Nonetheless, composting, vermicomposting, and biochar production pathways offer promising alternatives for managing this organic byproduct. Methods: BSG–based substrates were evaluated as bio–fertilizers for application during transplantation time and without additional fertilization input at the conclusion of crop cycle of Lactuca sativa L. Biochar (B), vermicompost (V), compost (CP), and compost enriched with a microbial consortium (CPE), each mixed at 2% and 4% with peat, were compared with two control treatments: 100% peat (C1) and peat with ternary chemical fertilizer (C2). The experiment was designed with six replicates, half of which were inoculated with Sclerotinia sclerotiorum mycelium at transplantation in order to assess the contribution of the different substrates to pathogen resistance. Results: Overall, the control treatment C2 was the most effective, yielding the greatest plant height at the seedbed stage and the best results across all parameters at harvest V 4%, CP 4%, and CPE 4% treatments showed similar results without significant differences compared to the control. At the end of the seedbed phase, plants treated with CP 4% and CPE 4% exhibited the most substantial root development, with statistically significant differences from all other treatments. Moreover, the CPE 4% treatment demonstrated superior performance, resulting in statistically significant differences (p<0.05) in chlorophyll content ( and ) and carotenoid parameters when compared to the control treatment C2. The interaction between treatment and pathogen was statistically significant only for the carotenoid content in the CPE 4% treatment and for the flavonoid content in most of the treatments. Discussion: The most promising results were obtained at the nursery phase, highlighting the potential use of processed BSG–based substrates as bio–fertilizers. These products supplied plants with both a growth substrate and nutrients, effectively addressing waste recycling and aligning with circular economy principles. Additional studies are required to investigate the potential use of brewer's spent grain as bio–fertilizers in other vegetable crop species.